'À la Carte' Peptide Shuttles: Tools to Increase Their Passage across the Blood–Brain Barrier. Issue 7 (24th March 2014) - Malakoutikhah, Morteza; Guixer, Bernat; Arranz‐Gibert, Pol; Teixidó, Meritxell; Giralt, Ernest
Abstract Noninvasive methods for efficient drug delivery to the brain is an unmet need. Molecular access to the brain is regulated by the blood–brain barrier (BBB) established by the endothelial cells of brain vessels. Passive diffusion is one of the main mechanisms that organic compounds use to travel through these endothelial cells. This passage across the BBB is determined mainly by certain physicochemical properties of the molecule such as lipophilicity, size, and the presence of hydrogen bond donors and acceptors. One emerging strategy to facilitate the passage of organic compounds across the BBB is the use of peptide shuttles.1 In using this approach the permeability in front the BBB is, clearly, determined by the combined physicochemical properties of both the cargo and the shuttle. Herein we report the synthesis of a series of variations of one of the more efficient peptide shuttles, (N‐MePhe)n. These include diverse structural features such as various backbone stereochemistries or the presence of non‐natural amino acids, including halogenated residues. In several cases, we assessed the BBB permeability of both the shuttles alone and linked to a few cargos. Our results show how factors such as stereochemistry or halogen content influences the passage across the BBB and, more importantly, opens the way to a strategy of peptide shuttles 'à la carte′, in which a particular fine‐tuned shuttle is used for each specific cargo.